A multi-scale approach to identify the role of heat treatment, milk protein composition and starter culture on the gel formation and the texture defects of acid milk gel. (December 2018) - Nguyen, An Thi-Binh; Nigen, Michaël; Jimenez, Luciana; Ait-Abderahim, Hassina; Cunault, Charles; Marchesseau, Sylvie; Picart-Palmade, Laetitia
Abstract: Two exocellular polysaccharide (EPS)-producing starter cultures, named B and C, were used to investigate the effect of (1) heat treatment, (2) supplementation in whey protein (WP) and (3) presence of EPS on the gel formation, gel microstructure and occurrence of texture defect, i.e. spontaneous syneresis and graininess, of acid milk gel. In skim milk (SM), culture B induced a slow acidification and produced a medium level of EPS (50 mg glucose kg −1 ). Heated at high temperature (95 °C, 6 min), the WP denaturation of the SM increased the syneresis of the gel and generated grains. Culture C had faster acidification kinetics and produced a higher quantity of EPS (80 mg glucose kg −1 ) that contribute to generating higher intrinsic viscosity to acid milk gel compare to culture B. Neither syneresis nor grain was observed in high heated SM gel obtained with culture C. The milk gel microstructure observed by confocal laser scanning microscopy showed that bacterial chains of culture B were short and embedded in the protein network while chains of culture C were longer, forming large clusters and mainly located in the gel pores. The overall results suggested that the presence of denatured WP is a cause of grain formation but that the curled chains of culture C surrounded by EPS could induce a steric hindrance during the gel structuring and prevent the growth of grain. The milk enrichment in WP increased the firmness, the water-holding capacity of acid gel but has generated graininess defect that could be reduced by the starter culture. Graphical abstract: Highlights: Kinetics of gelation and of EPS production during milk acidification were determined. Gel texture, gel microstructure and EPS properties molecular were characterized. Denatured WP aggregates were the cause of grain formation. Beside EPS, the bacterial morphology has also an important impact on gel texture. Long curled bacterial chains could prevent the graininess defect by steric hindrance.